Investigation of the Effect of Turboexpander on NOx Emissions - Fayaz, Farheen; Allport, John; Brace, Jordan (Engineering Science Letter, 2025)
As climate changes become more severe and the transition towards sustainability goals more important than ever, the need to modify our vehicles and their thermal management systems takes priority. The vast majority of Original Engine Manufacturers might be looking at the electrification of most vehicles, but it is equally important to make sure that our Internal Combustion Engine powered vehicles become more sustainable since most of our heavy transport is powered by ICEs. The biggest disadvantage of an ICE-powered vehicle is its emissions output. The engine emissions regulations have become stringent over the past few years leading to an increased emphasis on NOx reduction techniques. Air Cycle Technology (ACT) has created a novel form of turboexpander which has previously been tested by ACT in race car engines to reduce pre-ignition. This current work being reported has been carried out to prove the useability of the ACT turboexpander in diesel engines to reduce NOx formation by cooling the intake air. The engine used for this study is a 4.4-liter JCB-TCA 74 turbocharged diesel engine. The ACT turboexpander was retrofitted to the JCB engine. During the study performed on the JCB engine, second-stage cooling provided by the turboexpander showed a reduction of approximately 30° C in intake air temperatures. This data was also supported by hand calculations performed using empirical formulas.